Budaya Penegakan Hukum Anti-Korupsi: Membangun Kesadaran dan Keterlibatan Masyarakat di Indonesia - Shodiq, Mohamad Djafar; Muzakki, Fauzan (Ideas Publishing, 2025)
The problem of anti-corruption legal culture in Indonesia is a very complex issue and has many dimensions. Corruption not only damages the integrity of public institutions, but also reduces public trust in the government. In this case, it is important to realize that corruption is a systemic problem and requires a comprehensive approach to overcome, highlighting how social and cultural norms can support corrupt practices, emphasizing the importance of strategies that consider the local context, the formulation of the problem in this study is how effective the legal culture is in supporting anti-corruption law enforcement in Indonesia and the challenges it faces in controlling community behavior. This research methodology uses normative juridical with a legal enforcement theory framework by Roscoe Pound, a theory that aims to create harmony and harmony in society. The results of the study indicate that the importance of legal awareness: public awareness and discipline towards the law are greatly influenced by the norms that exist in society. Therefore, legal norms must be able to create shared expectations and mutual trust among members of society, cultural approach: developing corruption eradication strategies that are sensitive to local community norms and values, and introducing gradual cultural changes through public awareness campaigns and education